3. Interactivity as Artistic Mediation System. Installation and Participative Projects - Nae Oana Maria (Sciendo, 2022)
The first official step toward active participation and interaction was made by John Cage, Allan Kaprow, George Brecht, and other artists connected to the happening and Fluxus movements from 1950-1960. Since than the conceptual art maximizes the importance given to the shape and interaction as an artistic product. Essentially, the installations named environmental art bring before the visitor of the exhibition, the viewer, the entire sensory experience, more than the canvas centered on a "neutral" wall or on isolated objects on a pedestal. Analyzing some of this art works we discover that the installations leave the space and time in their usual size with a desire to highlight and understand the experience in a critical manner. This involves dissolving the border between art and life. These interactive installations have been succeeded in the next decade of participatory projects which supported the idea of reflection on the relationship of the individual with technology and the others, but also explored it with other resources, even more direct.